Mixed-sandwich Cp*Cr complexes containing poly(methimazolyl)borates (Cp* = C5Me5) : syntheses and structural and electrochemical studies - Kuan, Seah Ling (2013)
Reaction of the scorpionate salts K[HB(mt)3], Na[H2B(mt)2], and Li[HB(mt)2(pz)] with [Cp*CrBr2]2 (1) gave the 15-electron Cr(III) complexes [Cp*Cr{κ3-S,S′,S″-HB(mt)3}]Br (2), [Cp*Cr{κ2-S,S′-H2B(mt)2}Br] (3), and [Cp*Cr{κ2-S,S′-HB(mt)2(pz)}Br] (4) in moderate to high yields. These are the first examples of mixed-sandwich chromium(III) complexes containing poly(methimazolylborate) ligands. The tridentate coordination of the monoanionic ligands [H2B(mt)2] in 3 and [HB(mt)2(pz)] in 4 can be effected by using a silver salt to remove the Br coligand, thus yielding the complexes [Cp*Cr{κ3-H,S,S′-H2B(mt)2}]PF6 (6) and [Cp*Cr{κ3-N,S,S′-HB(mt)2(pz)}]PF6 (7). It was also found that, in the presence of acetonitrile, the reaction of 3 with AgPF6 afforded [Cp*Cr{κ2-S,S′-H2B(mt)2}(NCMe)]PF6 (5). The coordination geometries of all the complexes have been determined by X-ray diffraction analyses. Cyclic voltammetric studies of complexes 2, 4, and 7 showed that the oxidation and reduction processes are chemically reversible and that the reduced and oxidized states of complexes 3, 5, and 6 are very short-lived.